2022
DOI: 10.1111/jdv.18725
|View full text |Cite
|
Sign up to set email alerts
|

GBP5 exacerbates rosacea‐like skin inflammation by skewing macrophage polarization towards M1 phenotype through the NF‐κB signalling pathway

Abstract: Background: Rosacea is a chronic inflammatory skin disease with increased macrophage infiltration. However, the molecular mechanism remains unclear. Objectives: To determine the significance of macrophage infiltration, and the correlation between Guanylate-binding protein 5 (GBP5) and polarization of macrophages in rosacea-like inflammation. Methods: Here we tested the hypothesis that Guanylate-binding protein 5 (GBP5) aggravates rosacea-like skin inflammation by promoting the polarization of the M1 macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Therefore, macrophages in dura mater were observed at P42 when pro-inflammatory effect appeared in the CSF and hippocampus in IL-4 group. NF-κB signaling is the major pathway by which macrophage polarize towards M1 phenotype and F4/80 + /NF-κB + cells represent pro-inflammatory activation profile of macrophages (Wu et al 2022a ; Wang et al 2014 ; Zhou et al 2023 ). So we also observed the expression of NF-κB in dural macrophages by double labeling using immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, macrophages in dura mater were observed at P42 when pro-inflammatory effect appeared in the CSF and hippocampus in IL-4 group. NF-κB signaling is the major pathway by which macrophage polarize towards M1 phenotype and F4/80 + /NF-κB + cells represent pro-inflammatory activation profile of macrophages (Wu et al 2022a ; Wang et al 2014 ; Zhou et al 2023 ). So we also observed the expression of NF-κB in dural macrophages by double labeling using immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…OBE100 inhibits the expression of NFKBIZ, OSM, GBP5, IL1A, and IL6 genes in both human and mouse cells. NFKBIZ, a member of the ankyrin-repeat family and induced by lipopolysaccharide (LPS), OSM, a member of the IL-6 family of cytokines, and GBP5, a member of the dynamin superfamily of GTPases, are involved in the induction of inflammatory genes, including IL6 and IL1A [ [43] , [44] , [45] , [46] ]. IL6 encodes a cytokine that functions in inflammation and the maturation of B cells, and IL1A mediates the activation of NF-kappa B and the three MAPK pathways p38, p42/p44, and JNK pathways [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that M1 macrophage polarization promoted rosacea in ammation [17,30]. M1 macrophage polarization in rosacea may be the result of multiple factors.…”
Section: Discussionmentioning
confidence: 99%